Aktivitas Antiinflamasi Ekstrak Metanol Herba Puguntano (Picria fel-terrae Lour.) pada Tikus Putih Jantan yang Diinduksi λ-Karagenan - Vivi Asfianti; Vanny Yosepha Sagala; Andy Febriady; Suprianto; Shofian Syarifuddin (Yayasan Penelitian dan Inovasi Sumatera, 2026)
Background: Inflammation is a normal protective response to tissue injury caused by physical trauma, chemical exposure, or microbial agents. When excessive, this response may worsen tissue damage and require treatment. Interest in medicinal plants as alternative anti-inflammatory agents remains high because conventional nonsteroidal anti-inflammatory drugs, although effective, may cause adverse effects. Puguntano herb (Picria fel-terrae Lour.) contains flavonoids, saponins, tannins, glycosides, and steroids or triterpenoids that may contribute to anti-inflammatory activity. Objective: This study aimed to evaluate the anti-inflammatory effect of the methanolic extract of puguntano herb in male white rats with λ-carrageenan-induced paw edema and to identify the most effective tested dose. Methods: An experimental design was used in twenty-five healthy male rats divided into five groups. The negative control received 0.5% Na-CMC, the positive control received sodium diclofenac 2.25 mg/kg body weight, and the treatment groups received extract doses of 50, 100, and 200 mg/kg body weight. Acute inflammation was induced by intraplantar injection of 1% λ-carrageenan. Paw volume was measured with a digital plethysmometer for 360 minutes. Percentage of inflammation and percentage of inhibition were analyzed using one-way ANOVA followed by Tukey’s test. Results: The methanolic extract showed anti-inflammatory activity at all tested doses. A dose-dependent pattern was observed, with greater edema suppression at higher doses. The 200 mg/kg body weight dose produced the strongest effect and showed activity comparable to sodium diclofenac. Conclusion: The methanolic extract of puguntano herb demonstrated anti-inflammatory potential in this model, with the 200 mg/kg body weight dose as the most effective treatment for further preclinical study